Clinical differentiation of inflammatory bowel disease (IBD) in Latin America and the Caribbean. Issue 3 (21st January 2022) - Yamamoto-Furusho, Jesús K.; Parra-Holguín, Norma N.; Juliao-Baños, Fabián; Puentes, Fabián; López, Rocio; Bosques-Padilla, Francisco; Torres, Esther A.; Nieves-Jimenéz, Humberto; Veitia-Velásquez, Guillermo R.; Jara-Alba, Maria L.; Bautista, Sócrates; Piñol-Jimenez, Felipe N.; et al.
Abstract : Abstract: The aim of the present study was to describe the epidemiological and clinical characteristics of inflammatory bowel disease (IBD), including medical and surgical treatments, in several countries in Latin America and the Caribbean. IBD is recognized as a global health problem because its incidence and prevalence have increased significantly over the last few years. This multicenter retrospective cohort study included 4714 patients with IBD diagnosed from 9 countries in Latin America and the Caribbean: Colombia, Cuba, Dominican Republic, Ecuador, Mexico, Peru, Puerto Rico, Uruguay, and Venezuela. Crohn disease (CD) was more frequent in Puerto Rico (71.9%), the Dominican Republic (61.0%), and Peru (53.1%). Ulcerative colitis was more frequent in Colombia (78.6%), Venezuela (78.2%), Mexico (75.5%), Cuba (69.9%), Ecuador (64.1%), and Uruguay (60.9%). The following clinical characteristics were more frequent in the Caribbean: penetrating behavior in CD, steroid dependence, steroid resistance, intolerance to thiopurines, extraintestinal manifestations, surgeries, hospitalizations due to IBD, and family history of IBD. The factors associated with the use of biological therapy were pancolitis in ulcerative colitis, penetrating behavior in CD, steroid resistance and dependence, presence of extraintestinal manifestations, and the need for surgery. This study from Latin America and the Caribbean demonstrated the different epidemiological and clinical characteristics of IBD. Abstract : Supplemental Digital Content is available in the text